2017
DOI: 10.1021/acs.cgd.7b00041
|View full text |Cite
|
Sign up to set email alerts
|

Positional Isomerism and Steric Effects in the Self-Assemblies of Phenylene Bis-Monothiooxalamides

Abstract: The potential interplay of steric and substitution pattern effects of the monothiooxalamide side arms on the structure, conformational features, and self-assembly of a series of phenylene bis-monothiooxalamides was investigated. Herein we have demonstrated that phenylene bis-monothiooxalamides self-associate in the solid state, through intermolecular hydrogen bonding as meso-helices when the thioamide NR group is s Bu and through dispersive COwhen R is t Bu, independently from the substitution pattern in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…It is worth mention that this conformation has not been observed among organic cocrystals of H 2 pOXA but is commonly attained by coordination to metals [ 27 ]. The calculated conformational landscape of 1,4-phenylen dioxalyls predicts a very small difference in energy between planar ap - sp and sp - sp conformers of 0.26–0.28 kcal mol −1 , in favor of the former, and an interconversion energy of only 4.80 kcal mol −1 [ 16 ]. Then, the sp - sp conformation exhibited by the HpOXA − moiety is explained because of the stabilization given by hydrogen bonding with metformin that provides the energy to overcome the rotational barrier.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mention that this conformation has not been observed among organic cocrystals of H 2 pOXA but is commonly attained by coordination to metals [ 27 ]. The calculated conformational landscape of 1,4-phenylen dioxalyls predicts a very small difference in energy between planar ap - sp and sp - sp conformers of 0.26–0.28 kcal mol −1 , in favor of the former, and an interconversion energy of only 4.80 kcal mol −1 [ 16 ]. Then, the sp - sp conformation exhibited by the HpOXA − moiety is explained because of the stabilization given by hydrogen bonding with metformin that provides the energy to overcome the rotational barrier.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, both have attracted interest as coordinating ligands for metals [ 14 , 15 ]. Theoretical studies and experimental work [ 16 ] have demonstrated the high flexibility of the oxalic acid derivatives. Both oxalyl carbonyls are usually in anti disposition [ 17 ], but they less frequently adopt the syn disposition, induced by steric constraints [ 18 , 19 ] or by coordination with metals in the form of carboxylates [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 On the other hand, the phenyldioxalamate moiety has become particularly important as a versatile supramolecular building block exploited for the formation of a wide variety of supramolecular architectures. 5 For instance, diethyl N , N ′-1,3-phenyldioxalamates have been shown to form molecular clefts whose conformation and cavity size can be controlled by steric hindrance and hydrogen-bonding effects. 6 Furthermore, they have been used to explore the rotational isomerism of 1,3-benzenediols by cocrystallization.…”
Section: Introductionmentioning
confidence: 99%